Jurisdiction of a Labour Board

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryA Labour Relations Board has jurisdiction to hear an application before it, even if same of its members are absent, provided sitting members constitute a quorum. Members of the Board are not there to advocate the cause of the faction that they represented when appointed.British American Oil Company Limited, Applicant and The Saskatchewan Labour Relations Board, and, Oil, Chemical and Atomic Workers International Union, Local 16-595, Respondents, Court of Appeal, Province of Saskatchewan, Nov. 8th, 1960, Gordon, Acting C.J.S. for the Court.